Addressing Disparities in Stroke Prevention for Atrial Fibrillation: Educational Opportunities. (July 2016) - Karcher, Rachel; Berman, Adam E.; Gross, Hartmut; Hess, David C.; Jauch, Edward C.; Viser, Paul E.; Solenski, Nina J.; Wolf, Andrew M. D.
Disparities in atrial fibrillation (AF)-related stroke and mortality persist, especially racial disparities, within the US "Stroke Belt." This study identified barriers to optimal stroke prevention to develop a framework for clinician education. A comprehensive educational needs assessment was developed focusing on clinicians within the Stroke Belt. The mixed qualitative-quantitative approach included regional surveys and one-on-one clinician interviews. Identified contributors to disparities included implicit racial biases, lack of awareness of racial disparities in AF stroke risk, and lack of effective multicultural awareness and training. Additional barriers affecting disparities included patient medical mistrust and clinician-patient communication challenges. General barriers included lack of consistency in assessing stroke and anticoagulant-related bleeding risk, underuse of standardized risk assessment tools, discomfort with novel anticoagulants, and patient education deficiencies. Effective cultural competency training is one strategy to reduce disparities in AF-related stroke and mortality by improving implicit clinician bias, addressing medical mistrust, and improving clinician-patient communication.